Description of Moral Education According to Teens from Single Parent Family at Kenagarian Pauh Kambar, Kecamatan Nan Sabaris, Kabupaten Padang Pariaman - Silvi Yuli Andani; Syafruddin Wahid; Irmawita Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
This research is motivated by the good attitude of an adolescent from a single-parent family in Kenagarian Pauh Kambar, Nan Sabaris Sub-district, Padang Pariaman District. The purpose of this study is to describe moral education in terms of (1) moral reasoning, (2) moral behavior, and (3) moral personality. This type of research is descriptive quantitative. The population in this study amounted to 55 people. The sampling technique in this research is stratified random sampling. The number of samples in this study was 32 people. Data collection techniques used are questionnaires, while data collection tools use questions. Data analysis techniques using the formula percentage. The results showed that moral education according to adolescents from single-parent families is very good, it is seen from (1) moral reasoning, (2) moral behavior, and (3) moral personality. Suggestions for the moral education of these three aspects can be further enhanced by teens from single-parent families.Keywords: Moral Education, Teens Attitude, Single Parent Family